Der "Dilettant ohne Gesinnung". Zum Problem des Dilettantismus bei Joseph Roth - Schlosser, Jan (Nordlit, 2005)
The article focuses on the function of dilettantism in the works of Austrian author Joseph Roth. In his essays is the dilettant both the negative opposite to the "artist" and - more important - the classic dilettant, who plays with the world and many political point of views without reaching a total identification with them.